1982
DOI: 10.7164/antibiotics.35.1651
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel inhibitor of an aminoglycoside-inactivating enzyme.

Abstract: A novel low-molecular weight inhibitor of an aminoglycoside-inactivating enzyme, initially THE JOURNAL OF ANTIBIOTICS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…For instance, the chemically synthesized 4-Br-7HT is a potent inhibitor of multidrug resistant Acinetobacter baumanni (Cao et al, 2018). However, 7HT is currently produced only chemically by persulphate oxidation of tropolone, but it requires further purification to separate it from the byproducts 5HT, and 3,7-and 4,7dyhydroxytropolones (Nozoe et al, 1953;Kirst et al, 1982). Thus, bacterial production of 7HT may serve as an alternative source of precursor with sufficient purity for subsequent generation of novel derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the chemically synthesized 4-Br-7HT is a potent inhibitor of multidrug resistant Acinetobacter baumanni (Cao et al, 2018). However, 7HT is currently produced only chemically by persulphate oxidation of tropolone, but it requires further purification to separate it from the byproducts 5HT, and 3,7-and 4,7dyhydroxytropolones (Nozoe et al, 1953;Kirst et al, 1982). Thus, bacterial production of 7HT may serve as an alternative source of precursor with sufficient purity for subsequent generation of novel derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…34 The IC 50 value was not recorded, but at 100 µg/mL complete inhibition was observed, and close to 80% inhibition was seen for both compounds at 10 µg/mL. In addition, the compound was shown to work by competing with ATP for the enzyme.…”
Section: Metalloenzyme Inhibitionmentioning
confidence: 90%
“…The antimicrobial activity of 7-HT has so far been attributed to two features of this low-molecular weight compound: i) it is proven to be an inhibitor of enzymes, namely it suppresses the activity of aminoglycoside-inactivating enzyme [68] and inositol monophosphatase [69]; or ii) it acts as an iron chelator which possibly gives advantage to 7-HT producers in iron-deficient environments [20]. Our previous study showed that 7-HT contributes to the antibacterial effect of P482 against the selected strains of the Dickeya and Pectobacterium genera [10] under highly nutritional conditions such as LBagar or Tryptic Soy agar, since the 7-hydroxytropolone mutants (KN4705, KN4706 and KN4709) lost their antibacterial activity.…”
Section: Siderophore Biosynthesis As An Important But Not the Only Pamentioning
confidence: 99%